In silico modeling and structural analysis of asparaginyl endopeptidase of schistosoma mansoni (Sm32): Immunological and drug target implications. (February 2019) - Lorenzo, María Angelita; Gauna, Adriana Natalia; Herrera, Jholeisa; Bermúdez, Henry; Losada, Sandra; Noya, Oscar; Serrano, Maria Luisa
Graphical abstract: Highlights: The structure of the proenzyme form of Sm32 was determined by means of homology modeling and MD refinement. The charge distribution in the core and LSAM domains in Sm32 is different when compared to the AEs of mouse and human. The His151 of the catalytic dyad shows a hydrogen bond with Asp150 and a cation pi interaction with Arg52. In the active site, amino acid differences were identified in the β IV strand. IMT-26, a highly immunogenic fragment of the activation peptide, is considered for the development of diagnostic methods. Abstract: Asparaginyl endopeptidase (AE) of Schistosoma mansoni (Sm32), also known as legumain, is a cysteine protease indirectly involved in the digestion of hemoglobin of Schistosoma sp. in the gastrodermis, being a vaccine candidate against this trematode and a potential drug target. This study presents a model for the three-dimensional structure of Sm32 determined by means of homology modeling and a molecular dynamics simulation with explicit solvent refinement. The structure proved to be consistent with other AEs of known crystal structures described in their proenzyme form, revealing a catalytic domain that has a caspase-like overall structure and a C -terminal prodomain that adopts a death-domain-like architecture. We identified amino acid mutations in the βIV strand, differences in the active site and in the surface electrostatic potentials between Sm32 and its homologous proteins of mouse and human. Additionally, amino acid changes in the activation peptide (AP) of the S. mansoni protein were determined. Our results strongly suggest that Sm32 can be exploited as a potential target for drug design and for the development of biomarkers used in diagnosis and in novel vaccines for the control of parasitic infection, opening the perspective of medicinal chemistry developments.